(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
In Unani System of Medicine the drugs derived from natural sources are used, the majority of them are plant origin 85 %, animal origin 10% and mineral origin 5% but like any other system of medicine the efficacy of Unani System of Medicine also depends on potential and purity of the drugs used. To develop a mechanism for quality assurance of mineral compound to ensure the purity of crude drugs material and its standardization is essential. Standardization and quality control are the key factors in regulating the therapeutic efficacy of Unani Herbal drugs. Organoleptic parameters are often insufficient in the quality assessment of Unani Herbal Drugs. The present study deal with compound Unani formulation of Al-Ahmar is compound formulation of National Formulary of Unani Medicine Part 5. Al-Ahmar is a red colour powder therpeutically used in Zoof-e Bah and Qillat Shahwat Ba-sabab Broodat-e- Mizaj. Al-Ahmar is a natural product and is absolutely safe as it does not produce any side effects. In standardization of drugs, the drugs investigation through different chemical method, their active principale are being worked out, their percentage composition are as follow Alcohol soluble matter 0.70 %, Water soluble matter 3.60%, Bulk Density 4.88-5.00, Water content negligible, Mercury not more than 50 ppm and pH 10%: 8.28 & 1%: 8.51 is being determined and purity is confirmed. In addition analysis of Microbial Load, Aflatoxin and Pesticidal residue were also done but not detected.